PARTv: methodological guide to diagnose participation in television production - Hernández Alfonso, Eduardo Alejandro; Paz Enrique, Luis Ernesto; Alonso Freire, Joaquín (Cuadernos de Documentación Multimedia, 2018)
Local television is a means of communication close to its audience. The policies that govern the programming of these channels should enhance the participation of the public. The objectives of this research were: 1) to establish a methodological guide to diagnose the participation of the subjects involved in local television production, 2) to diagnose the participation of the subjects involved in the television production of the local television Centro Norte Televisión, Caibarién, Cuba.The study classifies as descriptive with theoretical character. The methods were used at the theoretical level: analytic-synthetic, systemic-structural, historical-logical, inductive deductive. At the empirical level were used observation, classical documentary analysis, statistical-mathematical method, survey and information triangulation. The techniques for the collection and representation of the results were the review of documents, the questionnaire and the analysis of social networks. A methodology was designed to diagnose participation in local television stations. The methodology designed through a case study was validated. The diagnosis of participation showed that there is a tendency to reproduce the unidirectional scheme of the classic communication model. It is recognized by Centro Norte Televisión that its publics have an active role in television production but they are not clearly distinguished in the documents consulted and in the social practice described. The expressions of participation identified limit the creativity of the subjects in the television production, because it does not recognize functions other than those established for each role.
Keywords: participation; television production; diagnosis of participation; methodological guide